EFEKTIVITAS PELATIHAN BERBASIS KOMPETENSI DI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN SUMEDANG - Akadun; Fadhli Firdani Taufik; Gahana Febri Syahrulloh; Imas Rinanda; Imey Meliawati; Lingga Chandra Pratama (JRPA - Journal of Regional Public Administration, 2021)
The purpose of this study was to determine whether or not the implementation of Competency-based training at the Department of Manpower and Transmigration in Sumedang Regency was effective, to find out what obstacles were faced, and to find out what efforts should be made to overcome the obstacles faced in the effectiveness of competency-based training.In this study, the method used is qualitative research methods with an inductive descriptive approach. The technique of determining research informants is purposive sampling. With research informants, namely the head of the field of training institutional development, section of training institute coaching, section of certification, competence and apprenticeship. Data collection techniques used are literature study and field study consisting of observation, interviews, and documentation. Meanwhile, the data processing techniques used are data reduction, data presentation, conclusion drawing verification, and triangulation.The results showed that the effectiveness of Competency-Based Training at the Manpower and Transmigration Office of Sumedang Regency was not yet effective because the training system had not been implemented properly. There are several obstacles faced in effectiveness, namely the number of employees who do not know competency-based training. The large number of employees who do not have special skills and still lack of provision of employee training and lack of awareness of employees of the importance of providing training to improve skills.